Project-Based Learning, Inquiry Methods, Demonstration Methods, and Psychomotor Abilities: A Review of the Literature - Lilies Esthi Riyanti; Cris Kuntadi; Bhima Shakti Arrafat; Iwan Engkus Kurniawan (Dinasti Publisher, 2023)
The psychomotor ability of students is one of the important aspects of the learning process. To achieve optimal psychomotor abilities, effective and efficient learning methods must be applied. This literature review article discusses three learning methods that affect students' psychomotor abilities: Project-Based Learning, Inquiry-Based Method, and Demonstration Method. Previous studies have shown that these three learning methods can help improve students' psychomotor abilities. Project-Based Learning can enhance the creativity and cooperation skills of students in a structured learning environment. The inquiry-Based Method can help students improve problem-solving and critical thinking skills through their experiments and discoveries. The Demonstration Method helps students acquire physical skills through observation and direct practice. Although these three learning methods have been proven effective, the selection of the appropriate learning method should be tailored to the characteristics of the students and the learning context.